Prostaglandins and Platelet Aggregation in Vivo - Kloeze, J (Thrombosis and Haemostasis, 1970)
It was shown previously that prostaglandin E1 (PGE1) inhibits the aggregation of blood platelets in vitro whereas PGF1α does not; in vivo, PGE1 inhibits in rats the action of intravenously injected adenosine diphosphate. Locally administered PGE1 is found in the present experiment to inhibit in rats the formation and growth of platelet thrombi, induced by an electric stimulus in cortical veins. PGF1α appeared to be inactive.The morphology of platelet thrombi induced by an electric stimulus is shown. The probability of a primary role of erythrocytes in the formation of this type of thrombi is discussed.